Pengaruh Kejenuhan Kerja, Konflik Kerja, dan Motivasi Kerja terhadap Turnover Intention pada Karyawan UMKM Azalea Food - Nazillah Layla Nur K; Siska Fajar Kusuma (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2024)
This study aims to determine the influence of work saturation, work conflict, and work motivation on turnover intention among Azalea Food employees. The research method used in this research is the survey method. Data collection uses direct observation and distribution of questionnaires in the field related to the research object. The population in this study were employees at Azalea Food. The sample in this research were employees at Azalea Food, which numbered 30 employees. This sampling used the saturated sampling method. The results of research using multiple linear regression analysis showed that partially work saturation, work conflict and work motivation had a significant positive effect on turnover intention among Azalea Food employees. Apart from that, simultaneously work burnout, work conflict, and work motivation have a significant positive effect on turnover intention among Azalea Food employees.